Coenzyme Q10 and pro-inflammatory markers in children with Down syndrome: clinical and biochemical aspects - Moushira E. Zaki; Hala T. El-Bassyouni; Angie M.S. Tosson; Eman Youness; Jihan Hussein
Abstract: Objective: Evidence of oxidative stress was reported in individuals with Down syndrome. There is a growing interest in the contribution of the immune system in Down syndrome. The aim of this study is to evaluate the coenzyme Q10 and selected pro-inflammatory markers such as interleukin 6 and tumor necrosis factor α in children with Down syndrome. Methods: Eighty-six children (5-8 years of age) were enrolled in this case-control study from two public institutions. At the time of sampling, the patients and controls suffered from no acute or chronic illnesses and received no therapies or supplements. The levels of interleukin 6, tumor necrosis factor α, coenzyme Q10, fasting blood glucose, and intelligence quotient were measured. Results: Forty-three young Down syndrome children and forty-three controls were included over a period of eight months (January-August 2014). Compared with the control group, the Down syndrome patients showed significant increase in interleukin 6 and tumor necrosis factor α (p = 0.002), while coenzyme Q10 was significantly decreased (p = 0.002). Also, body mass index and fasting blood glucose were significantly increased in patients. There was a significantly positive correlation between coenzyme Q10 and intelligence quotient levels, as well as between interleukin 6 and tumor necrosis factor α. Conclusion: Interleukin 6 and tumor necrosis factor α levels in young children with Down syndrome may be used as biomarkers reflecting the neurodegenerative process in them. Coenzyme Q10 might have a role as a good supplement in young children with Down syndrome to ameliorate the neurological symptoms.